Intimacy or exposure: Ukrainian artists and the camp wound in relations with Russia - Gajda, Kinga Anna; Kuryłowicz , Michał (Slavica, 2024)
The aim of the paper is to provide an interdisciplinary analysis of cultural testimonies of the unique wound left by the camps in Ukrainian–Russian relations. Gulag literature, explored for decades in philology, is perceived mainly through the prism of the heritage of totalitarian systems and creative attitudes in the face of suffering, as extreme physical and mental experience. The aim of the paper is to analyze the works of Ukrainian artists of recent decades created as a result of imprisonment. Their literary and film creations make up the image of a wound inflicted in the name of achieving imperial goals while imprisoned in a camp. The juxtaposition of their diverse artistic reactions to the suffering of testimonies help to highlight the power with which the unsettled, forgotten, silenced, and now and unexpectedly updated wound of the camp past is reflected in today’s attitudes of Ukrainians towards Russians.